La Gamificación y su influencia en la lectoescritura en el área de lengua y literatura bloque 3, lectura y escritura, en los estudiantes del cuarto grado paralelo “B” de la Escuela de Educación General Básica Miguel Riofrío de la ciudad de Loja, periodo lectivo 2021-2022. lineamientos alternativos. - Carrión Hurtado, Silvana Enith (2022)
The present research entitled Gamification and its influence on literacy in the area of Language and Literature, reading and writing, in the students of the fourth grade, block 3, classroom B, from Miguel Riofrio primary school, of the city of Loja, during the school year 2021-2022, alternative guidelines; aims to analyze the influence of gamification during the teaching-learning process of reading and writing, to contribute to their learning. This research is of great relevance since it allowed to identify the problems that certain students have, like reading and writing difficulties. In the same way, an instructive called Class Dojo was presented as a gamification tool with the purpose of helping students to read and write with the application of playful activities, which motivate them to learn in a fun way, thus students do not see it as an obligation. On the other hand, the research is descriptive, quantitative-qualitative, in which qualitative and quantitative data were collected, making use of scientific, descriptive, synthetic analytical, inductive, deductive, statistical and hermeneutic methods, through this research shows that exists a certain percentage of students who have difficulty reading and writing, which is associated with the different strategies that the teacher uses, which should be striking, thus the student feels motivated to experience new learning strategies. Keywords: Gamification, literacy, teaching - learning, motivation.